2013
DOI: 10.13076/tjo-d-13-00013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reliability of Three Different Computer-Assisted Analysis Programs

Abstract: The aim of this study was to assess the reliability of cephalometric analysis using 3 different digital analysis programs. Methods: For this study, a dry human skull with the entire mandible, maxilla, and teeth was used. Fifteen lateral and 15 posteroanterior cephalometric digital images were taken by rotating the skull from 08 to 6148 at 28 intervals to obtain different images. Two researchers located the landmarks on the digital images independently using 3 computer-assisted analysis programs, Dolphin Image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The agreement in landmark identification between the two examiners in this study was higher than that was reported by Uysal et al who had ICC values ranging from 0.484 to 0.727. The inter‐examiner correlations seen in this study were more consistent with those observed by Toy et al who presented correlation values between 0.836 and 0.990 ( P < 0.001 for both studies).…”
Section: Discussionsupporting
confidence: 92%
“…The agreement in landmark identification between the two examiners in this study was higher than that was reported by Uysal et al who had ICC values ranging from 0.484 to 0.727. The inter‐examiner correlations seen in this study were more consistent with those observed by Toy et al who presented correlation values between 0.836 and 0.990 ( P < 0.001 for both studies).…”
Section: Discussionsupporting
confidence: 92%